Activation of cellular immune response in insect model host Galleria mellonella by fungal α-1,3-glucan - Stączek, Sylwia (Pathog Dis, 2020)
Alpha-1,3-glucan, in addition to β-1,3-glucan, is an important polysaccharide component of fungal cell walls. It is reported for many fungal species, including human pathogenic genera: Aspergillus, Blastomyces, Coccidioides, Cryptococcus, Histoplasma and Pneumocystis, plant pathogens, e.g. Magnaporthe oryzae and entomopathogens, e.g. Metarhizium acridum. In human and plant pathogenic fungi, α-1,3-glucan is considered as a shield for the β-1,3-glucan layer preventing recognition of the pathogen by the host. However, its role in induction of immune response is not clear. In the present study, the cellular immune response of the greater wax moth Galleria mellonella to Aspergillus niger α-1,3-glucan was investigated for the first time. The changes detected in the total hemocyte count (THC) and differential hemocyte count (DHC), formation of hemocyte aggregates and changes in apolipophorin III localization indicated activation of G. mellonella cellular mechanisms in response to immunization with A. niger α-1,3-glucan. Our results, which have clearly demonstrated the response of the insect immune system to this fungal cell wall component, will help in understanding the α-1,3-glucan role in immune response against fungal pathogens not only in insects but also in mammals, including humans.